Persaingan Sumber Daya Alam: Konflik dan Intoleransi dalam Masyarakat - Muhammad Rafi Devrian; Dadi Mulyadi Nugraha; Ahmad Fu'adin; Amalia Diana Putri; Azmy Hanif Abdurrahman; Septian Dwi Kusuma (Jurusan Pendidikan Geografi Universitas Negeri Manado, 2023)
Competition for the use of natural resources often creates conflict between different communities and can lead to intolerance between them. This study aims to understand the competition for natural resources. This study uses a quantitative approach with data collection techniques through questionnaires with various people involved in the competition for natural resources in certain areas. The results of the research show that there has been competition for natural resources; this competition affects relations between communities; competition for natural resources creates intolerance; and intolerant attitudes and behaviors exacerbate resource competition. Intolerance is triggered by dissatisfaction and jealousy due to inequality in access to and utilization of natural resources, lack of participation in decision making, transparency and accountability in natural resource management. The effects of intolerance cause conflict, economic loss, and environmental damage.